Split Cas9, not hairs: advancing the therapeutic index of CRISPR technology - Schmelas, Carolin; Grimm, Dirk (Biotechnology journal, 2018)
The discovery that the bacterial CRISPR/Cas9 system can be translated into mammalian cells continues to have an unprecedented impact on the biomedical research community, as it largely facilitates efforts to experimentally interrogate or therapeutically modify the cellular genome. In particular, CRISPR promises the ability to correct disease-associated genetic defects, or to target and destroy invading foreign DNA, in a simple, efficient, and selective manner directly in affected human cells or tissues. Here, we highlight a set of exciting new strategies that aim at further increasing the therapeutic index of CRISPR technologies, by reducing the size of Cas9 expression cassettes and thus enhancing their compatibility with viral gene delivery vectors. Specifically, we discuss the concept of splitCas9 whereby the Cas9 holo-protein is segregated into two parts that are expressed individually and reunited in the cell by various means, including use of 1) the gRNA as a scaffold for Cas9 assembly; 2) the rapamycin-controlled FKBP/FRB system; 3) the light-regulated Magnet system; or 4) inteins. We describe how these avenues, despite pursuing the identical aim, differ in critical features comprising the extent of spatio-temporal control of CRISPR activity, and discuss additional improvements to their efficiency or specificity that should foster their clinical translation.
First published: 05 January 2018
Gesehen am 26.03.2020